Gender-Based Comparative Study Of The Influence Of Cola Nitida On Urine Calcium And Magnesium Concentrations Of Humans - Igbinovia Igbinovia; Edokpolor Nestor; Ohiwerei Wisdom Omogbai; Festus, Oloruntoba O.; Ibhadode Adesua; Echekwube Marylyn E (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
How Cola nitida could affect the urine calcium and magnesium concentrations of the male human subjects in comparison to the female counterpart were focused on. Sixty subjects (males=30 and females=30) and unaccustomed to Cola nut eating were involved. Their age range was between 18 and 28years. Three (3) sub-categories were involved: underweight=10, normal weight=10 and overweight=10. Hypertensive, renal and any subject with cardio-pulmonary-related conditions were exempted from the study. The normal chamber temperature, (RT=270C and RH=70%), the raised chamber temperature (RT =370C and RH=90%) were studied. Sequel to the foregoing, the subjects sat quietly in the sweat chamber for 20 minutes. The third experimental condition was the normal chamber temperature with exercise (RT=270C and RH=70%) and the subjects rode a bicycle ergometer at 750J/minute for 20 minutes. All of these happened prior to the consumption Cola nitida. Ahead of the experimentation in the sweat chamber, the subject urinated in a container in order for the timed urine volume to be measured and urine was again taken at the end of the experimentation that was also measured in order to obtain the actual urine volume within the given period. Thereafter, the urinary flow rate was calculated. The urine calcium and magnesium concentrations were likewise estimated. 0.5g/kg body weight of Cola nitida was given to each subject and chewed as a bolus. After swallowing, 50ml of deionized water was given to each subject to drink and the subject was allowed to rest for 90 minutes before being brought into the sweat chamber. The results showed that in respect to urine Ca ions concentration, no significant change was observed in a comparison between the males and females after the ingestion of Cola nitida under normal, raised temperature and exercise experimental conditions. As regards urine Mg ions concentration, no significant change was observed in a comparison between the males and females after the ingestion of Cola nitida under normal and exercise experimental conditions. However, there was a significant increase in Mg ions concentration in the female UW and NW subjects compared to the males after the consumption of Cola nitida under raised temperature condition.